Beliefs about public debt and the demand for government spending - Christopher Roth; Sonja Settele; Johannes Wohlfahrt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We examine how beliefs about the debt-to-GDP ratio affect people's attitudes towards government spending and taxation. Using representative samples of the US population, we run a series of experiments in which we provide half of our respondents with information about the debt-to-GDP ratio in the US. Based on a total of more than 4,000 respondents, we find that most people underestimate the debt-to-GDP ratio and reduce their support for government spending once they learn about the actual amount of debt, but do not substantially alter their attitudes towards taxation. The treatment effects seem to operate through changes in expectations about fiscal sustainability and persist in a four-week follow-up.
Keywords: P16; E60; Z13; 330; Government Debt; Political Attitudes; Beliefs; Expectations; Information